Copyright Issues Relating to Database Use - Gupta, V.K. (DESIDOC Journal of Library & Information Technology, 2002)
Databases are being created for dissemination of information in varioussectors such as industry, tourism and hotel, culture development, planning,agriculture, health, environment, science and technology, geography,population, etc This paper focusses on issues related to copyright protectionof these databases. http://dx.doi.org/10.14429/dbit.17.4.3227